Racial differences in lifestyle, demographic, and health factors associated with quality of life (QoL) in midlife women - Brandi Patrice Smith; Esmeralda Cardoso-Mendoza; Jodi A. Flaws; Zeynep Madak-Erdogan; Rebecca L. Smith (BMC, 2021)
Abstract Previously, quality of life (Qol) has been defined as an individual's evaluation of a satisfactory life as a whole (i.e. physically, mentally, psychologically, and socially). Only a few studies have examined the racial differences between QoL and risk factors associated with health, demographics, and lifestyle in midlife women. Thus, the purpose of our study was to determine racial differences in QoL in menopausal women due to lifestyle, demographic, and health related risk factors. A stratified ordinal logistic regression model was applied to self-reported questionnaire data from the Midlife Women's Health Study (MWHS) to determine risk factors associated with QoL differences between White and Black women during the menopausal transition. In multivariable models, our results showed Black women who had 3 or 4 comorbidities were about 4 times as likely to have higher QoL compared to women who had 0 to 2 comorbidities (95% CI: 1.65,10.78). However, the number of comorbidities was not significantly associated with QoL in White women in univariate or multiple regression. Further, body mass index and income were not significant factors in QoL in Black women but were in White women. Overall, our results illustrate that differences in health, demographic, and lifestyle factors are associated with QoL during menopause. Also, we suggest that future studies evaluate stratified models between racial groups to determine race-specific risk factors related to quality of life.